2021
DOI: 10.1021/acs.langmuir.1c02461
|View full text |Cite
|
Sign up to set email alerts
|

From Microurchins to V2O5 Nanowalls: Improved Synthesis through Vanadium Powder and Fast, Selective Adsorption of Methylene Blue

Abstract: Research on synthesizing micro- and nanosized materials directly from metals has attracted considerable attention because of its simplicity, ability to synthesize in large quantities, and high uniformity. This study proposes a simple method to synthesize high-uniformity or high-density V2O5 microurchins and nanowalls directly from vanadium powder. Remarkably, the synthesis condition of 60 °C for 1 h is considered to be an optimal condition to convert metals into micro- or nano-oxides. The as-synthesized V2O5 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…19 Hien et al have reported up to 90% MB adsorption in 3 min with 117 mg g −1 of adsorption capacity by using vanadium(V) oxide (V 2 O 5 ) nanowalls. 20 Surface hydroxyl group enriched titanium dioxide (TiO 2 ) nanotubes (TNT) were demonstrated to remove 87.7% of MB dye due to the electrostatic interaction between the cationic dye MB and the negatively charged TNT surface. 21 Similarly, mixed oxide nanoparticles (NPs) of Al, Si, and Ti were shown to have a dye adsorption capacity of 162.92 mg g −1 in 30 min due to the presence of a mixed amorphous anatase phase with increased hydroxyl and Si–O δ − groups on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 Hien et al have reported up to 90% MB adsorption in 3 min with 117 mg g −1 of adsorption capacity by using vanadium(V) oxide (V 2 O 5 ) nanowalls. 20 Surface hydroxyl group enriched titanium dioxide (TiO 2 ) nanotubes (TNT) were demonstrated to remove 87.7% of MB dye due to the electrostatic interaction between the cationic dye MB and the negatively charged TNT surface. 21 Similarly, mixed oxide nanoparticles (NPs) of Al, Si, and Ti were shown to have a dye adsorption capacity of 162.92 mg g −1 in 30 min due to the presence of a mixed amorphous anatase phase with increased hydroxyl and Si–O δ − groups on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hình 7 là đồ thị thể hiện khả năng hấp phụ của 5 mg V2O5 với các chất màu hữu cơ được đưa ra so sánh. Từ kết quả nghiên cứu cho tại hình 7, có thể khẳng là phù hợp để giải thích tại sao V2O5 có hiệu suất hấp phụ thấp với các chất màu trên[18]. Cơ chế hấp phụ hoá học (tương tác tĩnh điện) của V2O5 đối với MB được thể hiện thông qua phản ứng sau: V2O5-O -+ C16H18N3S + → V2O5-O --S + -N3C16H18…”
unclassified